Low Frequency Current Ripple Reduction Technique With Active Control In A Power System With Inverter Load (International Journal of Engineering and Computer Science, 2017)
During the next few years there will be a profound change in the generation and usage of energy, influenced factors such as environment, capital and production costs as well as geopolitical factors, old power stations in the world will be phased out. Newer power stations, having large output capacity will be difficult to permit in many existing political climates. With global warming now apparent, environment and efficient fuel utilization have become significant factors in the adaptation of newer and emerging energy conversion technologies. High installation cost is the major obstacle of the commercialization of fuel cell for distributed power generation. A fuel cell power system that contains a dc–ac inverter tends to draw an ac ripple current at twice the output frequency. Such a ripple current may shorten input cell lifespan and worsen the efficiency and output capacity. In this paper, an advanced active control technique is proposed to incorporate a current control loop in the dc–dc converter for ripple reduction. This will reduce both size and cost of the system. The proposed active ripple reduction method has been verified with MATLAB simulation.